2021
DOI: 10.1007/s11548-021-02470-6
|View full text |Cite
|
Sign up to set email alerts
|

A virtual reality simulator for training the surgical reduction of patient-specific supracondylar humerus fractures

Abstract: Purpose Virtual reality has been used as a training platform in medicine, allowing the repetition of a situation/scenario as many times as needed and making it patient-specific prior to an operation. Of special interest is the minimally invasive plate osteosynthesis (MIPO). It represents a novel technique for orthopedic trauma surgery, but requires intensive training to acquire the required skills. In this paper, we propose a virtual reality platform for training the surgical reduction of supraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…At present, VR and AR simulators can help students to perform better [ 38 40 ]. But the data collection capabilities of them are limited.…”
Section: Discussionmentioning
confidence: 99%
“…At present, VR and AR simulators can help students to perform better [ 38 40 ]. But the data collection capabilities of them are limited.…”
Section: Discussionmentioning
confidence: 99%
“…For complex articular fracture patterns, a computed tomography (CT) with 3D reconstruction could be helpful in preoperative evaluation and accurate reduction planning [ 36 , 37 ]. Some authors presented good results after using a virtual reality-based simulator for training the reduction of the fracture [ 38 ]. Also, the use of artificial intelligence (AI) has been used for fracture detection, but its algorithms must be better tested [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The innovative minimally invasive plate osteosynthesis (MIPO) approach in orthopaedic trauma surgery requires substantial training for adequate skill acquisition. A VR platform was developed by Negrillo-Cárdenas et al for training in the MIPO technique for surgical reduction of humeral supracondylar fractures [ 64 ]. It was shown that the common malrotation of MIPO-treated fractures might be avoided by enhancing the motor skills and expertise of surgeons via an emphasis on the mobility of bone fragments.…”
Section: Vr Systems For Bone Trauma Proceduresmentioning
confidence: 99%